2012
DOI: 10.1053/j.gastro.2011.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cdc25A Suppresses Hepato-renal Cystogenesis in Rodent Models of Polycystic Kidney and Liver Disease

Abstract: Background & Aims In polycystic kidney (PKD) and liver (PLD) diseases, the normally non-proliferative hepato-renal epithelia acquire a proliferative, cystic phenotype, which is linked to overexpression of Cdc25A and cell cycle deregulation. We investigated the effects of Cdc25A inhibition in mice and rats, via genetic and pharmacological approaches. Methods Cdc25A+/− mice (which have reduced levels of Cdc25A) were cross-bred with Pkhd1del2/del2 mice (which have increased levels of Cdc25A and develop hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
1
28
0
1
Order By: Relevance
“…Levels of cAMP are elevated in cystic cholangiocytes [21] influencing cellular pathways known to be defective in PLD. Several examples include: (i) cell proliferation involves cAMP down-stream effectors, such as EPAC1, EPAC2, PKA and ERK1/2 [21, 22]; (ii) expression of the cell cycle proteins is cAMP-regulated [23]; (iii) fluid secretion into cystic lumen is enhanced in response to cAMP elevation and requires the water channel AQP1 and the ion transporters, CFTR and AE2 [24]; and (iv) cilia in cystic cells lack the components of the cAMP signaling pathway (e.g., adenylyl cyclase 5/6, A kinase anchoring protein 150 (AKAP150), PKA and phosphodiesterase 4C) subsequently interrupting cross-talk between cAMP and intracellular calcium; as a result cholangiocyte proliferation and cyst growth are increased. Importantly, a number of studies suggest that targeting the components of the cAMP machinery in cystic cholangiocytes attenuates hepatic cystogenesis.…”
Section: Therapeutic Targets In Pldmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of cAMP are elevated in cystic cholangiocytes [21] influencing cellular pathways known to be defective in PLD. Several examples include: (i) cell proliferation involves cAMP down-stream effectors, such as EPAC1, EPAC2, PKA and ERK1/2 [21, 22]; (ii) expression of the cell cycle proteins is cAMP-regulated [23]; (iii) fluid secretion into cystic lumen is enhanced in response to cAMP elevation and requires the water channel AQP1 and the ion transporters, CFTR and AE2 [24]; and (iv) cilia in cystic cells lack the components of the cAMP signaling pathway (e.g., adenylyl cyclase 5/6, A kinase anchoring protein 150 (AKAP150), PKA and phosphodiesterase 4C) subsequently interrupting cross-talk between cAMP and intracellular calcium; as a result cholangiocyte proliferation and cyst growth are increased. Importantly, a number of studies suggest that targeting the components of the cAMP machinery in cystic cholangiocytes attenuates hepatic cystogenesis.…”
Section: Therapeutic Targets In Pldmentioning
confidence: 99%
“…The cell cycle profiles of cystic cholangiocytes are different from control cells likely resulting from the over-expression of the master cell cycle regulator, Cdc25A [23]. Cdc25A overexpression is associated with an increased proportion of cholangiocytes that have atypical centrosomal positioning, supernumerary centrosomes, multipolar spindles and extra cilia [43].…”
Section: Therapeutic Targets In Pldmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the last decade, intense efforts are being focused on understanding the molecular mechanisms involved in the pathogenesis of these diseases in order to find new pharmacological targets for medical treatment [2] . In this regard, hepatic cystogenesis involves DPM [10] , increased cholangiocyte proliferation [11,12] and secretion [13] , ciliary and centrosomal abnormalities [14] , altered cell-matrix interaction [15] , neoangiogenesis [16] , global microR-NA dysregulation [17] , and all of these features are associated with increased cyclic adenosine monophosphate (cAMP) levels [18] and decreased calcium (Ca 2+ ) concentration [11,19] in cystic cholangiocytes. Of note, the role of bile acids in the pathophysiology of PLDs is currently attracting significant attention.…”
mentioning
confidence: 99%
“…We previously showed that both pasireotide and VK3 affected hepatic and renal cystogenesis in PCK rats and Pkd2 WS25/ -mice. 3,5,8 We also studied the chemical chaperone, sodium 4-PBA, which suppresses endoplasmic reticulum (ER) stress by chemically enhancing the ER capacity to cope with the expression of misfolded proteins. Both proteins implicated in cystic liver disease (sec63 and prkcsh) reside in the ER and are involved in the processing of glycoproteins to prevent protein misfolding or retention of proteins in the ER.…”
mentioning
confidence: 99%